Sistem Informasi Akuntansi Penjualan dan Penerimaan Kas Berbasis Komputer Pada Rumah Sehat MKK Bersinar - Nurkholijah, Fadillah; Fadila , Zakia (Jurnal Sains dan Teknologi, 2023)
A company requires an accounting information system to handle daily operational activities and produce accounting information required by management and other related parties concerning decision-making and other policies. This research aims to analyze the implementation of the sales and cash receipts accounting information system and the effectiveness of the sales and cash receipts accounting information system used by Rumah Sehat MKK Bersinar. The method used in this research is a qualitative method with descriptive analysis, with data collection techniques through interviews and literature study. Next, carry out a system analysis of the accounting information system design and then create a sales and cash receipts accounting information system. The result of this research is that the implementation of the sales and cash receipts accounting information system at Rumah Sehat MKK Bersinar can provide information for the owner through the system and the sales and cash receipts accounting information system is not yet effective because there still weaknesses in its internal control, namely supervision of the information system.